2018
DOI: 10.17343/sdutfd.431726
|View full text |Cite
|
Sign up to set email alerts
|

Küçük Hücreli Dışı Akciğer Kanseri Hastalarında Onkogen Mutasyonlarının Araştırılması

Abstract: Yüksek insidansa sahip olan Küçük Hücreli Dışı Akciğer Kanseri (KH-DAK) en yüksek mortaliteye sahip kanser alt tipi olarak önemini korumaktadır. Çoğunlukla belirtilerin ileri evrelerde kendini göstermesi tedavi başarısını önemli ölçüde kısıtlamaktadır. Son yıllarda, tümör dokusunda meydana gelen genetik değişiklikler sonucu ortaya çıkan onko-proteinlerin baskılanabilmesi tedavi başarısına önemli katkı sağlamıştır. Tümördeki bu moleküler değişimlerin tespiti kişiye özgü tedavilerin ön plana çıkmasına katkı sağl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In our study, we found at least one gene mutation in 15.8% (n=52) of the patients. High mutation detection rate in the studies of Çalıskan et al (9) and Bilgin et al (10) may be related to the low number of patients and the more specific patient selection. Although the true incidence of EGFR mutation in lung cancers is unknown, the incidence varies between 0 and 13% (11,12).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In our study, we found at least one gene mutation in 15.8% (n=52) of the patients. High mutation detection rate in the studies of Çalıskan et al (9) and Bilgin et al (10) may be related to the low number of patients and the more specific patient selection. Although the true incidence of EGFR mutation in lung cancers is unknown, the incidence varies between 0 and 13% (11,12).…”
Section: Discussionmentioning
confidence: 96%
“…While the incidence of EGFR, ALK, ROS1 and BRAF mutations in patients with adenocarcinoma is approximately 30% in the Uninted States of America, this rate is 60% in Japan (7,8). Çalıskan et al (9) detected at least one gene mutation in 37 (46.2%) of 80 patients with lung cancer in a Turkish population. Bilgin et al (10) detected at least one gene mutation in 60 (22.9%) of 260 NSCLC patients and EGFR was positive in 38 (14.6%), ALK was positive in 20 (7.69%), and ROS1 was positive in 2 (0.76%) of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation